Two new species of the Cybaeus hiroshimaensis-group (Araneae: Cybaeidae) from the northern Hida Mountains, Japan - Nakano, Takafumi; Ogawa, Gakuto; Mori, Kei; Hatanaka, Yu; Koike, Naoki; Sugawara, Yusuke (Soil Organisms, 2025)
Two small-sized species of the spider genus Cybaeus L. Koch, 1868, C. pycnothrix sp. nov. and C. tateyamensis sp. nov., are described based on both sexes from the Tateyama Mountain Range in the Hida Mountains, central Honshu, Japan. Phylogenetic analyses using nuclear internal transcribed spacer 1, 28S rRNA, and histone H3 markers revealed that the two new species are members of the monophyletic Japanese Cybaeus hiroshimaensis-group. Both new species conform to the morphological diagnosis of the hiroshimaensis-group — small body size and a short, thick male palp — and build two-opening retreats, indicating that retreat architecture in the group varies and encompasses both two- and three-opening forms.
Keywords: Arachnida; RTA clade; core Cybaeidae; molecular phylogeny